THE ROLE OF BEHAVIORAL ACCOUNTING IN BUDGETARY CONTROL OF PUBLIC CORPORATIONS IN INDONESIA - Yofy Syarkani (GoAcademica Research dan Publishing, 2024)
This article explores the role of behavioral accounting in enhancing budgetary control within public corporations in Indonesia. As public sector organizations face increasing demands for accountability and efficiency, understanding the psychological and behavioral aspects influencing financial decision-making has become crucial. Behavioral accounting, which integrates insights from psychology and organizational behavior, offers a nuanced perspective on budgeting practices beyond traditional financial metrics. This literature review synthesizes findings from peer-reviewed journals, institutional reports, and theoretical frameworks to identify key behavioral factors affecting budgeting effectiveness. The study highlights how cognitive biases, leadership styles, motivation, and communication dynamics influence budget preparation, implementation, and monitoring. Moreover, it examines the alignment between behavioral accounting practices and Indonesia’s bureaucratic and regulatory environment. Through a thematic analysis of the selected literature, the paper identifies common challenges such as resistance to budget targets, lack of participatory processes, and psychological ownership issues. The review also draws comparative insights from international practices to contextualize Indonesia’s experience. Ultimately, the study proposes strategic implications for integrating behavioral insights into public financial management. This article contributes to the discourse on reforming public sector accountability by emphasizing the human dimensions of budgetary control.